Analisis Strategi Pemasaran Menggunakan Metode SWOT dan QSPM Pada PT Bumi Citra Property - Sari, Sindia; Indah Sari, Chitra (Program Studi Manajemen FEBM UMRAH, 2023)
The purpose of this study was to determine the marketing strategy using the SWOT and QSPM methods at PT Bumi Citra Property. The research method used is field research with a mixed quantitative and qualitative approach. In this study SWOT analysis was used to determine the strengths, weaknesses, opportunities and threats at PT Bumi Citra Property which will be measured by the IFE Matrix, EFE Matrix, IE Matrix and SWOT Matrix. Then the best alternative strategy is selected which must be prioritized using the QSPM method. The problem in this research is PT Bumi Citra Property's low sales and the decline in sales that occurred at PT Bumi Citra Property can be seen in 2017-2022 due to the impact of covid 19, promotions that have not been optimally carried out and similar business competition which has resulted in non-achievement Predetermined home sales targets. Based on the research results it is known that the marketing strategy at PT Bumi Citra Property uses Grow and Build. Where the results of the IE matrix analysis show that the highest score is in quadrant I, then the SWOT matrix obtains ten alternative strategies that will be taken into account using the QSPM matrix so that strategic priorities are obtained, namely maximizing product promotion through offline and online media on a regular basis so that housing products are better known to the public by TAS score 2.868.